Analisis Disposisi Matematis pada Pembelajaran Matematika di Sekolah Dasar - Syaripah, Syaripah; Putri, Janega Kencana; Rahmadeni, Fevi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The problems of this research are students' lack of attention to the teacher's explanation, lack of enthusiasm for lessons and their lack of curiosity in mathematics lessons. Then, the aims of this research are to know students’ mathematical disposition and the results of the mathematical disposition of students at grade 5 SDIT Khoiru Ummah after using the CORE (Connecting, Organizing, Reflecting, Extending) learning model. The type of the research was quantitative descriptive research. The population was 63 students with a sample of 30 students using purposive sampling. The data collection technique was in the form of observation and a questionnaire consisting of 20 questions referring to 5 indicators of mathematical disposition. The second data used had been validated by experts. From the research results of applying the CORE (Connecting, Organizing, Reflecting, and Extending) learning model to the mathematical disposition of grade 5 students at SDIT Khoiru Ummah, it was shown that teacher and students’ activities are very good. The results of the students' mathematical disposition obtained from the questionnaire were classified as high as many as 23 people, medium as many as 4 people and low as many as 3 people.